Net neutrality and inflation of traffic - Martin Peitz; Florian Schuett (University of Mannheim, Department of Economics, 2015)
Under strict net neutrality Internet service providers (ISPs) are required to carry data without any differentiation and at no cost to the content provider. We provide a simple framework with a monopoly ISP to evaluate different net neutrality rules. Content differs in its sensitivity to delay. Content providers can use congestion control techniques to reduce delay for their content, but do not take into account the effect of their decisions on the aggregate volume of traffic. As a result, strict net neutrality often leads to socially inefficient traffic in ation. We show that piece-meal departures from net neutrality, such as transmission fees or prioritization based on sensitivity to delay, do not necessarily improve efficiency. However, allowing the ISP to introduce bandwidth tiering and charge for prioritized delivery can implement the efficient allocation.
urn:nbn:de:bsz:180-madoc-375355
Keywords: L12; L51; L86; 330; Net neutrality; network congestion; telecommunications; quality of service